2023
DOI: 10.26655/jmchemsci.2023.7.6
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A series of some new heterocyclic compounds containing triazin derivatives have been synthesized in many steps sequence. Triazine derivatives were prepared through reacting benzil with semicarbazide or thiosemicarbazide to form 5,6-diphenyl-1,2,4-triazin-2(3H)one,5,6-diphenyl-1,2,4-triazine-2(3H)thione, respectively. A hydroxymethylation reaction has been made to the amide group. The hydroxyl group was replaced by azide group. A different substituted triazine rings have been formed using different reagents. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Premenstrual symptoms disrupt a female's regular lifestyle during the luteal phase of the menstrual cycle and resolve once the menstrual cycle starts [16]. Literature studies have shown a high prevalence rate of premenstrual symptoms among women with a high level of psychosocial stress.…”
Section: Discussionmentioning
confidence: 99%
“…Premenstrual symptoms disrupt a female's regular lifestyle during the luteal phase of the menstrual cycle and resolve once the menstrual cycle starts [16]. Literature studies have shown a high prevalence rate of premenstrual symptoms among women with a high level of psychosocial stress.…”
Section: Discussionmentioning
confidence: 99%